Vessels for “River-Sea” Shipping Technologies - Jaromir Klepoch; Pavel Zarnay (Communications - Scientific letters of the University of Zilina, 2001)
Inland and marine water transport intersect each other in seaside areas of continents as well as in off-shore parts of world seas and oceans. That leads to their natural technological and technical integration. In the largest possible extent is this shown on the water transport means, which is a ship or eventually also a formation of vessels in various technological configuration. In that way, transport systems which are a part of combined systems of water transport named as“river-sea”, are created. In these systems, apart from dimensionally smaller marine ships, which are able to navigate also into river-sea ports situated deeply in big rivers mouths, two basic alternatives of ”river-sea” vessels can be distinguished.